Improvement of Information Technology Undergraduate Thesis Project - Tiwow, Gilly Marlya; Batmetan, Johan Reimon; Rumagit, Selvie Serly; Katuuk, Deitje Adolfien; Usoh, Elni Jeini; Lengkong , Jeffry Sony Junus (JR Education, 2023)
Many students face challenges in the thesis preparation process, including time constraints, lack of integration with industry requirements, and lack of understanding of research methodology. This research aims to formulate another form of student thesis project with equal reasoning and difficulty level that can be measured and converted as a thesis. Apart from that, it also improves the quality and relevance of undergraduate thesis projects in Information Technology. The research method used is a descriptive approach, involving surveys and interviews. Research participants include Information Technology undergraduate students, supervisors, industry practitioners, and advisory boards. Data collection instruments include a structural questionnaire and interview guide designed to explore experiences, perceptions, and suggestions regarding changes in the preparation of the thesis project. The proposed solution involves implementing effective time management, closer integration with industry challenges through partnerships with companies, increased understanding of research methodologies, and adaptation of curricula to reflect dynamic changes in the Information Technology industry. It is hoped that the results of this research can provide concrete guidance for improving thesis projects and creating graduates who are better prepared and relevant to industry needs. Through this approach, it is hoped that this research can contribute to improving the academic process in producing higher quality and relevant thesis projects in the context of information technology.